2019
DOI: 10.1111/1365-2435.13360
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic responses to genomic selection for timing of breeding in a wild songbird

Abstract: The physiological mechanisms underlying avian seasonal timing of reproduction, a life‐history trait with major fitness consequences, are not well understood. Comparing individuals that have been selected to differ in their timing of breeding may prove to be a promising in studying these mechanisms, making selection lines a valuable tool. We created selection lines for early and late timing of breeding in great tits (Parus major) using genomic selection, that is selection based on multi‐marker genotypes rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 93 publications
5
47
0
Order By: Relevance
“…The selection line study results are reported elsewhere (Verhagen et al, 2019). Briefly, we found that on average early-line birds laid their eggs about 6 days earlier than late-line birds.…”
Section: Materials and Methods Selection Lines In The Timing Of Breedingsupporting
confidence: 55%
See 2 more Smart Citations
“…The selection line study results are reported elsewhere (Verhagen et al, 2019). Briefly, we found that on average early-line birds laid their eggs about 6 days earlier than late-line birds.…”
Section: Materials and Methods Selection Lines In The Timing Of Breedingsupporting
confidence: 55%
“…Briefly, we found that on average early-line birds laid their eggs about 6 days earlier than late-line birds. Further, the difference in average laying date increased (from about 2 to 10 days) from the F 1 to the F 3 generation, with non-significant line effects for the F 1 and F 2 generation, but highly significant line differences for the F 3 generation (Verhagen et al, 2019).…”
Section: Materials and Methods Selection Lines In The Timing Of Breedingmentioning
confidence: 93%
See 1 more Smart Citation
“…We used the great tit, a well-known model species in ecology and evolution with a reference genome 25 , SNP arrays (10k 42 and 650k 43 ), and whole transcriptome and methylome for various tissues 25,41,44 . The individuals included are part of a bidirectional selection experiment for early and late reproduction using genomic selection 45,46 (details in methods S1). For the experiment, we housed 36 breeding pairs of the F2 generation in climate-controlled aviaries mimicking natural temperature and photoperiod patterns of a cold and warm year in the Netherlands 47,48 .…”
Section: Methodsmentioning
confidence: 99%
“…This is possible because laying date is a heritable (polygenic) trait (Van der Jeugd and McCleery 2002;. Such a selection experiment was recently completed in great tits (Parus major) originating from the Dutch Hoge Veluwe population (see Gienapp et al 2019;Verhagen et al in review for details of this selection experiment). Female offspring of birds that were selected to breed either early or late in outdoor aviaries exhibited extreme genomic breeding values and concomitant different phenotypes between early-and lateline birds in captivity (Verhagen et al in review).…”
Section: Introductionmentioning
confidence: 99%